Resolving the issue of missing persons with reference to the role of the international community - Krstić Ljiljana; Milović Marko M. (Megatrend Revija, 2021)
The existence of the problem of missing persons is a necessary consequence of armed conflicts, even conflicts that arose on the territory of the former Yugoslavia. After twenty years or more, we still have a fairly large number of wanted persons who are listed as missing. The attempts of the international community to help solve these painful issues, which especially concern their families and which arose both during and after the armed conflict, especially in Croatia and on the territory of Kosovo and Metohija, were pointed out. In this regard, a review was given of the Declaration on the Role of the State in Resolving the Issue of Missing Persons from 2014, which was signed by four countries in the region and which should be an incentive in resolving this issue.